Metabolite profiling of natural substances in human: in vitro study from fecal bacteria to colon carcinoma cells (Caco-2) - Racova, Zuzana; Anzenbacherova, Eva; Papouskova, Barbora; Poschner, Stefan; Kucova, Pavla; Gausterer, Julia Clara; Gabor, Franz; Kolar, Milan; Anzenbacher, Pavel (The Journal of nutritional biochemistry, 2020)
Flavonoids, including anthocyanins, are polyphenolic compounds present in fruits, vegetables and dietary supplements. They can be absorbed from the intestine to the bloodstream or pass into the large intestine. Various bacterial species and enzymes are present along the entire intestine. The aim of the present work was to investigate the intestinal metabolism of selected dietary polyphenol and polyphenol glycosides (quercetin, cyanidin-3-O-glucoside, cyanidin-3-O-galactoside, and delphinidin-3-O-galactoside) by human fecal bacteria. Moreover, the metabolism of metabolites formed from these compounds in human colon carcinoma cells (Caco-2) was also point of the interest. Test compounds were added to fresh human stool in broth or to Caco-2 cells in medium and then incubated for 6 or 20 h at 37°C. After incubation, samples were prepared for LC/MS determination. Main metabolic pathways were deglycosylation, hydrogenation, methylation, hydroxylation, and decomposition. 2,4,5-trihydroxybenzaldehyde, as a metabolite of cyanidin glycosides, was detected after incubation for the first time. Metabolites formed by fecal bacteria were further glucuronidated or methylated by intestinal enzymes. This metabolite profiling of natural compounds has helped to better understand the complex metabolism in the human intestine and this work also has shown the connection of metabolism of natural substances by intestinal bacteria followed by metabolism in intestinal cells.
Keywords: Caco-2 Cells; Feces; Metabolomics; glykosidy; Bacteria; Human; Caco-2; Caco-2 buňky; Glycosides; polyfenoly; metabolom; Metabolic Networks and Pathways; Intestinal Mucosa; Polyphenols; flavonoidy; Metabolome; Fecal bacteria; nádory tračníku; Flavonoids; feces; Humans; Colonic Neoplasms; střevní sliznice; metabolické sítě a dráhy; lidé